To Study the Visual Outcomes and Intraocular Pressure Changes After Nd: Yag Laser Capsulotomy for Posterior Capsular Opacification - Dr. Divjot Kaur; Dr. Akash; Dr. Gurpreet Kaur; Dr. Arpita; Kashishpreet Kaur, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: To evaluate the visual outcomes and intraocular pressure (IOP) changes following Nd:YAG laser capsulotomy in patients with posterior capsular opacification (PCO) after cataract surgery. Methods: A prospective study was conducted on 100 patients with visually significant PCO at a tertiary care center. Inclusion criteria included age 40–80 years, prior cataract surgery with posterior chamber intraocular lens (PCIOL) implantation, and no pre-existing glaucoma or retinal pathology. Nd:YAG laser capsulotomy was performed using standardized energy settings (1.5–2.5 mJ). Pre- and post-procedure assessments included best corrected visual acuity (BCVA), IOP measurement, and fundus examination at 1 hour, 1 week, 1 month, and 3 months post-procedure. Results: Mean BCVA improved from 6/36 pre-procedure to 6/9 post-procedure, with 88% of patients maintaining BCVA ≥6/9 at 3 months. Transient IOP spikes (≥5 mmHg) occurred in 12% of patients at 1 hour, all managed successfully with topical medications. Mean IOP stabilized to baseline (15.8 ± 2.3 mmHg) by 1 month. Cystoid macular edema (2%) and floaters (8%) were observed, with no cases of retinal detachment or sustained IOP elevation. 92% reported high satisfaction with visual outcomes. Conclusion: Nd:YAG laser capsulotomy significantly improves visual acuity in PCO patients with minimal complications. Transient IOP spikes are manageable, and the procedure is safe for appropriately selected patients.